2002
DOI: 10.1007/bf03344072
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione peroxidase (GPX) activity in seminal plasma of healthy and infertile males

Abstract: Human spermatozoa are more dependent on glutathione peroxidase/glutathione reductase (GPX/GR) system, via reduced glutathione (GSH), to inactivate reactive oxygen metabolites (ROMs) such as hydrogen peroxide and organic hydroperoxides. To demonstrate whether there is a substantial difference in GPX activity between normal and pathological seminal plasma, we decided to evaluate the activity of this enzyme in healthy subjects and infertile males with normal hormonal patterns. Our results demonstrate that in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 19 publications
2
18
0
2
Order By: Relevance
“…This significant raise of seminal LPO in abnormal groups can be explained by the significant decrease of the enzymatic antioxidant activities (SOD, GPX and CAT) in infertile groups. These observations corroborated with the findings of [6,7,18,24] and highlighted the fundamental scavenging activity of these antioxidant enzymes against the oxidation of membrane lipids and the loss of sperm membrane integrity [28,34]. Moreover, we have clearly indicated that lowered antioxidant profile and elevated seminal MDA concentrations were closely associated with increased sperm DFI.…”
Section: Discussionsupporting
confidence: 78%
“…This significant raise of seminal LPO in abnormal groups can be explained by the significant decrease of the enzymatic antioxidant activities (SOD, GPX and CAT) in infertile groups. These observations corroborated with the findings of [6,7,18,24] and highlighted the fundamental scavenging activity of these antioxidant enzymes against the oxidation of membrane lipids and the loss of sperm membrane integrity [28,34]. Moreover, we have clearly indicated that lowered antioxidant profile and elevated seminal MDA concentrations were closely associated with increased sperm DFI.…”
Section: Discussionsupporting
confidence: 78%
“…Although a number of studies have investigated the relationship between human seminal plasma GPX and semen parameters, results have not been consistent. Lower GPX levels have been reported among infertile men (27,28), as well as in patients with asthenozoospermia (29), while in other studies no relationship between these parameters was detected (30)(31)(32), and, surprisingly, in another study, higher levels of GPX were reported in males with oligozoospermia or asthenozoospermia (33). These discrepancies may be explained by sample sizes.…”
Section: Discussionmentioning
confidence: 89%
“…This mouse exhibits an age dependent increase in oxidative damage to sperm DNA which is, in turn, associated with high rates of miscarriage in mated females as well as birth defects in the offspring. Male factor infertility has been linked with a reduction in seminal plasma [163] and spermatozoa [164] GPX activity, further supporting an important role for this enzyme in male fertility. In addition, men exhibiting leukospermia-associated oxidative stress have been reported to have significantly reduced GPX activity within their spermatozoa [165].…”
Section: Endogenous Antioxidantsmentioning
confidence: 93%